Antidiabetic activity of tannin fraction of Bridelia ferruginea (Benth) leaf extract on fructose-induced diabetic mice - Sabrina Sanvee; Oudjaniyobi Simalou; Gneiny Whad Tchani; Hèzouwè Kagnou; Batomayena Bakoma; Kossi Metowogo; Kokou Agbékonyi Agbodan; Kafui Kpegba (Shahrekord University of Medical Sciences, 2021)
Introduction: Bridelia ferruginea is a plant known for its antidiabetic properties. However, few studies on leaf extracts have induced anti-hyperglycemic activity on normal mice subjected to carbohydrate overload. The current study was designed to assess the effect of the leaf extracts' fraction on fructose-induced diabetic mice. Methods: The in vitro ferric-reducing antioxidant power (FRAP) assay were carried out and the condensed tannins quantified. The vanillin-HCl method was used to characterize the condensed tannins. The antidiabetic effect on fructose-induced diabetic mice was evaluated for 28 days using a fructose-enriched fat diet approach. Results: The fraction confirmed the antioxidant activity with a reducing power of 800 μg/mL comparable to ascorbic acid at 200 μg/mL. The condensed tannins were estimated at 79.6 ± 3.4 mg catechin equivalent per gram of sample. Significant decreases in blood sugar levels of 6.25% at the 7th day, 11.04% at the 14th day, 12.61% at the 21th day, and 11.35% at the 28th day were obtained in mice treated with the extract dose of 200 mg/kg of body weight, compared to the positive control group. The decreases of 37.11% of triglycerides and 40.16% of total cholesterol were also obtained. Conclusion: The investigated fraction showed notable antidiabetic activity and might be a good candidate in the treatment of diabetes.